2008
DOI: 10.1021/ja8012598
|View full text |Cite
|
Sign up to set email alerts
|

Compositional and Electric Field Dependence of the Dissociation of Charge Transfer Excitons in Alternating Polyfluorene Copolymer/Fullerene Blends

Abstract: The electro-optical properties of thin films of electron donor-acceptor blends of a fluorene copolymer (PF10TBT) and a fullerene derivative (PCBM) were studied. Transmission electron microscopy shows that in these films nanocrystalline PCBM clusters are formed at high PCBM content. For all concentrations, a charge transfer (CT) transition is observed with absorption spectroscopy, photoluminescence, and electroluminescence. The CT emission is used as a probe to investigate the dissociation of CT excited states … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

65
683
3
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 562 publications
(752 citation statements)
references
References 109 publications
65
683
3
1
Order By: Relevance
“…Recently, the existence of an intermediate charge transfer (CT) state between the exciton and the free charges in some blend systems based on polyfluorene has been reported. [62][63][64] Understanding the nature of such an intermediate state and its dependence on blend composition is important in understanding the effect of microstructure on charge generation. As an example, Veldman et al confirmed the existence of a charge transfer (CT) state in the blend of a fluorene copolymer (PF10TBT) ''poly[2,7-(9,9-dialkylfluorene)-alt-5,5-(4 0 ,7 0 -di-2-thienyl-2 0 ,1 0 ,3 0 -benzothiadiazole)] with PCBM.…”
Section: Blend Compositionmentioning
confidence: 99%
“…Recently, the existence of an intermediate charge transfer (CT) state between the exciton and the free charges in some blend systems based on polyfluorene has been reported. [62][63][64] Understanding the nature of such an intermediate state and its dependence on blend composition is important in understanding the effect of microstructure on charge generation. As an example, Veldman et al confirmed the existence of a charge transfer (CT) state in the blend of a fluorene copolymer (PF10TBT) ''poly[2,7-(9,9-dialkylfluorene)-alt-5,5-(4 0 ,7 0 -di-2-thienyl-2 0 ,1 0 ,3 0 -benzothiadiazole)] with PCBM.…”
Section: Blend Compositionmentioning
confidence: 99%
“…As a result, the measured spectrum is usually composed of the PL from both the pristine materials and CT states. [45][46][47] …”
Section: Absorptionmentioning
confidence: 99%
“…CT state EL was first reported by Kim et al, 48 and then also observed by other groups (Figure 2c). 46,47,49 Although the EL of the CT state is in the same spectral range as the PL, the EL peak usually shows slight redshift compared with the PL peak. 50 In addition, the EL peak could also show slight blueshift with increasing injection current or applied voltage.…”
Section: Electroluminescencementioning
confidence: 99%
“…The question, of what the polaron pair generation yield in pristine donor-acceptor co-polymers actually is, remains largely unanswered while being of very large relevance for understanding and improving photovoltaics. For example, discrepancies between theoretically predicted solar cell efficiencies, based on Onsager-Braun models, and the higher measured values may originate from the previously disregarded contribution of polaron pairs forming directly in the polymer 2,7 .…”
mentioning
confidence: 97%
“…Light absorption by the polymer has been largely improved towards the near infrared (NIR) spectral region by the introduction of low-bandgap co-polymers 4,5 . Exciton dissociation, however, remains to be understood and has recently been the subject of several investigations [6][7][8][9][10] .…”
mentioning
confidence: 99%